Production of Lime from the Limestone of Isparta Region, Turkey - TANRIVERDI, MEHMET; KARAKUS, DOGAN; KONAK, GURCAN (Asian Journal of Chemistry, 2010)
Lime is a material that has been widely used over the ages. The existence of lime has been proven by the fact that the earth crust contains 3.5-4 % limestone and magnesium. Different types of limestone are present in various formations on the earth crust. They vary in their colour, chemical composition, texture, crystal type and hardness. Some special properties are expected from the lime according to the purpose of usage in industry. In this study, the properties of the limestone sample provided from Isparta distinct are examined, in order to study the possibility of lime production.